Determinants of lease rents of village ponds for aquaculture: evidence from Central Gujarat [An abstract] - Kuriachen, Philip; Basu, S.; Choudhury, Arnab Paul; Verma, Shilp; Shah, Tushaar (Indian Society of Agricultural Economics, 2024)
The fishery sector in the country is undergoing a remarkable transformation, with India now being the second-largest fish producer in the world, and fish becoming the highest-exported item from India. Despite the sector’s growth, challenges persist for smallholders, limiting their productivity and curbing livelihood opportunities. Maximizing profitability is imperative amidst rising input costs. One key factor identified in this study is the lease rent paid for community ponds allocated to farmers. By focusing on Central Gujarat’s village pond leasing policy, the study examines the dynamics surrounding the auctioning of village ponds and the factors influencing them. Contrary to other states, Gujarat employs an open auction policy for village ponds to encourage competitive bidding among interested parties. However, the prevalence of information asymmetry on pond values among bidders hinders auction efficacy, leading to inefficient allocation. The study hypothesizes that auctions for village ponds resemble common value auctions, where bidders face uncertainty regarding the true value of the asset. Identifying the determinants of bidder valuation and integrating them into the determination of upset prices can mitigate information asymmetry, enhance auction efficacy, and reduce adverse selection. The study also identified considerable variance between the bid values of different ponds. On average, the bid value comprises 25 per cent of the total cost for a fish farmer in Anand district of Gujarat, with a tremendous difference between the highest and lowest bid values per hectare. While the highest bid value of the surveyed pond was Rs 1.7 lakh/hectare, the lowest bid value was recorded at Rs 900/hectare. This huge variance in bid value data and contributing factors was considered a crucial area of exploration. The study deployed Directed Acyclic Graphs and Linear Regression methodologies to identify the extent of this influence. The key findings could inform strategies to address such cost constraints, ultimately empowering smallholders to capitalize on opportunities within this rapidly evolving sector. By optimizing the auction process, stakeholders can unlock the full potential of village ponds, driving inclusive growth and sustainable development in India’s fisheries sector.